Effect of Temperature on Drug Release: Production of 5-FU-Encapsulated Hydroxyapatite-Gelatin Polymer Composites via Spray Drying and Analysis of In Vitro Kinetics - Nalan Erdöl Aydin (International Journal of Polymer Science)
In this study, 5-fluorouracil- (5-FU-) loaded hydroxyapatite-gelatin (HAp-GEL) polymer composites were produced in the presence of a simulated body fluid (SBF) to investigate the effects of temperature and cross-linking agents on drug release. The composites were produced by wet precipitation at pH 7.4 and temperature 37°C using glutaraldehyde (GA) as the cross-linker. The effects of different amounts of glutaraldehyde on drug release profiles were studied. Encapsulation (drug loading) was performed with 5-FU using a spray drier, and the drug release of 5-FU from the HAp-GEL composites was determined at temperatures of 32°C, 37°C, and 42°C. Different mathematical models were used to obtain the release mechanism of the drug. The morphologies and structures of the composites were analyzed by X-ray diffraction, thermal gravimetric analysis, Fourier transform infrared spectroscopy, and scanning electron microscopy. The results demonstrated that for the HAp-GEL composites, the initial burst decreased with increasing GA content at all three studied temperatures. Further, three kinetic models were investigated, and it was determined that all the composites best fit the Higuchi model. It was concluded that the drug-loaded HAp-GEL composites have the potential to be used in drug delivery applications.